WMO evaluation of northern hemispheric coldest temperature: −69.6 °C at Klinck, Greenland, 22 December 1991. (23rd September 2020) - Weidner, George; King, John; Box, Jason E.; Colwell, Steve; Jones, Phil; Lazzara, Matthew; Cappelen, John; Brunet, Manola; Cerveny, Randall S.
Abstract: A World Meteorological Organization (WMO) Extremes Evaluation Committee investigated an observation of −69.6 °C by Klinck Automatic Weather Station (AWS) in Greenland on 22 December 1991 as the lowest temperature observed in Greenland, thereby making it the lowest recorded near‐surface air temperature for the Northern and Western Hemispheres and for WMO Region VI. The committee examined the metadata and observations of the station as well as the regional synoptic circulation. The committee concluded that the observation is credible in terms of instrument calibration, monitoring of the station and the synoptic situation. Consequently, the WMO Rapporteur accepted the observation as the officially lowest observed near‐surface air temperature for Greenland, the Northern and Western Hemisphere and for WMO Region VI. As a supplement to this investigation, the committee also recommends that opportunities be investigated such that AWS data from Greenland can be efficiently incorporated into real‐time weather forecasts and hence into reanalysis datasets. Abstract : A World Meteorological Organization (WMO) Extremes Evaluation Committee investigated and accepted an observation of −69.6 °C by Klinck Automated Weather Station (AWS) in Greenland on 22 December 1991 as the lowest temperature observed in Greenland, thereby making it the lowest recorded temperature for the Northern and Western Hemispheres and for WMO Region VI. Additionally, the committee also recommends that opportunities be investigated such that AWS data from Greenland can be efficiently incorporated into real‐time weather forecasts and hence into reanalysis datasets.